Vietnam constitutional law: development orientationestablishment and development orientation - Phan, Thanh Ha (Đại học Quốc Gia Hà Nội, 2020)
The establishment and development of the Vietnamese Constitutional Law science is associated with the development stages of the Constitutions. These are: (1) The period from 1945 to 1986: an important opening stage of the Constitutional Law science, institutionalizing the ideas about the State and law, civil rights, people’s life, and so on into the regulations in the Constitutions of 1946, 1959 and 1980. (2) From 1986 to 1992: marking the development of Vietnam Constitutional Law Science during the Doi Moi period, with the birth of the Constitution of 1992 and the increase in research on state power, state management, democracy, and People’s right to mastery. (3) From 1992 to 2013: The period during which Vietnam Constitution Law Science focused on clarifying the role and meaning of the provisions of the Constitution and the law as a basis for comprehensive renewal of social life in the country. (4) From 2013 to present: featuring research on the provisions of the new Constitution and organizing the implementation of the Constitution. While pointing out the approach, research methods and research forces, the authors of this article also shed light on the content of the research on the Constitutional Law science in each period based on which, some major research directions for the Vietnam Constitution Law science in the new period are suggested.Due to historical circumstances, from 1954 to 1975, Vietnam was divided into two regions, with two different political regimes. In the framework of the paper and research conditions, the authors will only mention the scientific history of the Constitutional Law of the Democratic Republic of Vietnam (from 1946 to 1976) and the Socialist Republic of Vietnam (from 1976 to the present)